An Unusual Case of Primary Extranodal Lymphoma of the Gallbladder - Pezzuto, Roberto (Hematol Rep, 2017)
Primary gallbladder lymphoma is an extremely rare disease. We report a case of a 63 year-old woman who has been admitted with gradual onset abdominal pain in the upper right quadrant and in the suprapubic region, nausea and malaise. According to the computed tomography scan of the abdomen, which was suggestive of chronic cholecystitis, she was treated conservatively. A laparoscopic cholecystectomy was performed 5 months later and the histological examination of the gallbladder showed a low grade small lymphocytic lymphoma. The patient has been taken over by the hematology team who kept her under surveillance as no further treatment was deemed as necessary. The purpose of this paper is to report a rare case of primary gallbladder lymphoma and to demonstrate that a laparoscopic cholecystectomy may be a valid treatment for this disease.